Integration of Wifi and Mobile Communications in Fire Early Warning Data Sending in Home Based on The Internet of Things - Tamrin, Fadli; Asrul, Asrul; Arman, Arman (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
House fires are one of the most frequent disasters in dry climates, with impacts that not only cause material losses but also cause loss of life. This research aims to develop a fire early warning system that integrates WiFi and cellular communication technology to provide a fast and accurate response. The methods used include black-box testing and hardware testing using Arduino Mega2560, ESP32, DHT-22, MQ-2, LDR Array, SIM900, Mini DC Pump, and Mini DC Fan. The test results show that the system can operate both online and offline, where each sensor is able to detect indications of fire, gas, and smoke in real time. Furthermore, this device is designed not only for household applications but also has the potential for use on an industrial scale. This innovation makes an important contribution to disaster risk mitigation efforts by increasing community preparedness, accelerating the evacuation process, and minimizing losses. Thus, the developed system serves as a practical and applicable solution to create a safer and more resilient environment against the threat of fire.